A darkling plain : stories of conflict and humanity during war - Monroe, Kristen Renwick, 1946-; Lampros-Monroe, Chloe; Pellecchia, Jonah Robnett (Cambridge : Cambridge University Press, 2015)
How do people maintain their humanity during wars? Despite its importance, this question receives scant scholarly attention, perhaps because war is overwhelming. The generally accepted belief is that wars bring out the worst in us, pitting one against another.'War is hell', William Tecumseh Sherman famously noted, and even'just' wars are massively destructive and inhumane. Since ethics is concerned with discovering what takes us to a morally superior place, one conducive to betterment and happiness - studying what helps people survive wartime trauma thus becomes an extremely valuable enterprise. A Darkling Plain fills an important scholarly void, analyzing wartime stories that reveal much about our capacity to process trauma, heal wounds, reclaim lost spirits, and derive meaning and purpose from the most horrific of personal events.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: War -- Moral and ethical aspects; War -- Psychological aspects; Humanity -- Philosophy